Expanding the Roles of Libraries: A Review of Institutional Repository in Promoting and Preserving Academic Research - Ali Benson & Dauda Abigail, Moruf Hawwau A., Okolo Omachi (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2019)
Institutional repository is a new scholarly publishing model for researchers and academic institutions. The idea is conceived to enable broader access and dissemination of knowledge as well as preservation for future use, which are the core roles of traditional libraries. However, digital technology facilitates the adoption of institutional repository and makes libraries responsible for its management. Thus, libraries have reclaimed their function of preserving knowledge which has hitherto been hindered by digital right management policies whose emphasis is on access rather than ownership, and which has prohibited libraries from claiming ownership of subscribed materials. Institutional repository roles in enhancing academic research, faculty-librarian collaboration, library services and collections, as well as the roles of libraries in promoting and preserving academic research knowledge for posterity cannot be undermined. To achieve these laudable roles, preservation policy for repositories is of paramount importance. The study thus provides a review of different literatures to explore the key roles of institutional repositories in promoting academic research. The review of literature revealed that lack of adoption of repository policies pose challenges to institutional repositories in the preservation of academic research. The analysis of the Registry of Open Access Repository Mandates and Policies (ROARMAP) statistics showed a partial adoption of repository policies among research institutions. It is recommended that adoption of preservation policies for repository content should spread across borders and form prerequisite for establishing institutional repositories. This review suggested other factors to consider in improving the implementation of institutional repository policies towards preserving academic research.